2003
DOI: 10.1021/jo034628e
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Trans Dihydroxylation of Nonactivated C−C Double Bonds of Aliphatic Heterocycles withSphingomonassp. HXN-200

Abstract: The bacterial strain Sphingomonas sp. HXN-200 was used to catalyze the trans dihydroxylation ofN-substituted 1,2,5,6-tetrahydropyridines 1 and 3-pyrrolines 4 giving the corresponding 3,4-dihydroxypiperidines 3 and 3,4-dihydroxypyrrolidines 6, respectively, with high enantioselectivity and high activity. The trans dihydroxylation was sequentially catalyzed by a monooxygenase and an epoxide hydrolase in the strain with epoxide as intermediate. While both epoxidation and hydrolysis steps contributed to the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…6 Both routes require a large number of steps to afford the desired compound in low overall yields. Recently, Chang et al 9 have reported the preparation of the optically pure trans-isomers using enantioselective transdihydroxylations or epoxidations of N-substituted 1,2,5,6-tetrahydropyridines, catalyzed by the bacterial strain Sphingomonas sp. HXN-200.…”
Section: Introductionmentioning
confidence: 99%
“…6 Both routes require a large number of steps to afford the desired compound in low overall yields. Recently, Chang et al 9 have reported the preparation of the optically pure trans-isomers using enantioselective transdihydroxylations or epoxidations of N-substituted 1,2,5,6-tetrahydropyridines, catalyzed by the bacterial strain Sphingomonas sp. HXN-200.…”
Section: Introductionmentioning
confidence: 99%
“…The three fused P450cam-RhFRed variants were screened against a panel of substrates, which were selected on the basis of the potential application of their oxidation products. For instance, the terpenes α- and β-ionone and their derivatives have been widely used for the synthesis of carotenoids or in the fragrance industry [2326], and functionalized aliphatic heterocycles are versatile building blocks for further elaboration, e.g., by biocatalytic means [27]. …”
Section: Resultsmentioning
confidence: 99%
“…HXN‐200, affording the corresponding trans ‐diols 34 and 35 with high enantioselectivities. This cascade reaction is sequentially catalyzed by a monooxygenase and an epoxide hydrolase (Scheme ) …”
Section: Anti‐dihydroxylation With Epoxide Intermediatesmentioning
confidence: 99%